Prototype Monitoring Penyiraman Otomatis Pada Tanaman Tomat Berdasarkan Kelembapan Tanah Menggunakan Esp8266 Berbasis Iot - salawati; farida; sri asfirawati khalik (Institut Teknologi dan Bisnis Bina Adinata, 2025)
This research aims to: (1) To design a prototype for monitoring automatic watering of tomato plants using the IoT-based Esp8266. (2) To know how to build a monitoring prototype of automatic watering on tomato plants based on soil moisture using IoT-based ESP8266. This study uses the Prototype research method, where the stages are as follows: (1) needs analysis. (2) make a prototype (3) evaluate the prototype (4) code the system (5) test the system (6) evaluate the system (7) use the system. Based on the results of this study it can be concluded that : (1) Prototype monitoring automatic watering of tomato plants based on soil moisture using the iot-based Esp8266 is designed using soil moisture sensors, Esp8266, relay, water pump, jumper cabels, adpters and using the blynk application. The soil moisture sensor will detect soil moisture then it will be processed by the Esp8266 microcontroler to then be forwared to the relay to disconnect or connect the current to the water pump so that water can flow and notifications go to blynk (2) The prototype for monitoring automatic watering of tomato plants based on soil moisture using the iot-based Esp8266 was built in the form of a prototype with tomato plants provided in pots where the soil moisture sensor will detect soil moisture which will work in three humidity conditions, namely conditions <=60% (pump flush), 61-80% (safe state), >80% condition (ecessive fatigue) and notification goes to blynk and based on the results of the validation it get value 0,87 was found that all the aspects that were declared had very high validation, so that the working process of the tool worked optimally